A Comparative Evaluation of Community Periodontal Index (CPI) and the Presence of Nicotine Stomatitis among Smokers after Oral Hygiene Instruction - Meta Maulida Damayanti; Yuktiana Kharisma; Fajar Awalia Yulianto; Santun Bhekti Rahimah; Winni Maharani; Meike Rachmawati; Herri S. Sastramihardja; Muhammad Alief Abdul ‘Aziiz; Muhammad Ilham Halim (Universitas Islam Bandung, 2020)
Smoking can cause periodontal disease as well as lesions in the oral mucosa. Nicotine stomatitis is inflammation caused by heat stimuli injury on the hard and soft palate of the oral cavity; smokers commonly suffer from this condition. Knowledge of how oral hygiene affects the health of dental and oral cavity. The purpose of this study was to describe the differences in community periodontal index (CPI) and nicotine stomatitis in smokers after oral hygiene instruction. The study subjects were 54 men who have a history of active smoking for more than five years. The experiment was carried out in the Biomedical Laboratory of Faculty of Medicine Universitas Islam Bandung in September 2018–January 2019. Dental examination initiated before and after dental health instructions. CPI and nicotine stomatitis tests performed on all subjects by dentists using dental instruments. After six weeks of information about oral hygiene, all subjects re-examined. The results show that there is a statistically significant difference in the average CPI value in smokers before and after dental instruction with a p value<0.001 (p≤0.05). In contrast, the condition of nicotine stomatitis remains the same. CPI value influenced by oral and dental hygiene showed that dental health instruction is very effective. However, stomatitis has not healed as long as the cause is not eliminated. EVALUASI KOMPARATIF COMMUNITY PERIODONTAL INDEX (CPI) DAN STOMATITIS NIKOTIN DI KALANGAN PEROKOK SETELAH INSTRUKSI KEBERSIHAN MULUTMerokok dapat menyebabkan penyakit pada periodontal maupun lesi pada mukosa mulut. Stomatitis nikotin merupakan inflamasi yang disebabkan oleh panas yang terdapat pada palatum keras dan lunak; perokok umumnya menderita kondisi ini. Pengetahuan mengenai tata cara kebersihan mulut memengaruhi kesehatan gigi dan rongga mulut. Tujuan penelitian ini menilai perbedaan community periodontal index (CPI) dan stomatitis nikotin pada perokok setelah instruksi kebersihan mulut. Subjek penelitian adalah 54 pria yang memiliki riwayat merokok aktif selama lebih dari lima tahun. Penelitian dilakukan di Laboratorium Biomedik, Fakultas Kedokteran, Universitas Islam Bandung pada bulan September 2018–Januari 2019. Pemeriksaan dental dilakukan sebelum dan setelah instruksi kesehatan gigi. Pemeriksaan CPI dan stomatitis nikotin dilakukan kepada seluruh subjek oleh dokter gigi menggunakan instrumen gigi. Setelah enam minggu mendapatkan penyuluhan mengenai kebersihan mulut, seluruh subjek diperiksa kembali. Hasil penelitian menunjukkan bahwa terdapat perbedaan bermakna secara statistik nilai CPI rerata pada perokok sebelum dengan setelah dilakukan instruksi kesehatan gigi dengan p<0,001 (p≤0,05). Sebaliknya, kondisi stomatitis nikotin tetap sama. Nilai CPI dipengaruhi oleh kebersihan gigi dan mulut sehingga instruksi kesehatan gigi sangat efektif. Akan tetapi, stomatitis tidak dapat sembuh selama penyebabnya tidak dihentikan.